Phenotypic Spectrum of Granular Corneal Dystrophy Type II in Two Italian Families Presenting an Unusual Granular Corneal Dystrophy Type I Clinical Appearance - Cosimo Mazzotta; Claudio Traversi; Stefano Baiocchi; Stefano Barabino; Alessandro Mularoni (Case Reports in Ophthalmological Medicine)
Clinical, instrumental, and genetic findings are reported in Italian families with Type II Granular Corneal Dystrophies (GCD2) presenting an initial unusual presentation of a Granular Corneal Dystrophy Type I (GCD1) phenotypic spectrum in female descendants. Slit-lamp examinations showed the typical phenotypic features of GCD2 in both mothers and a phenotypic appearance of GCD1 in both daughters. Despite the different phenotypic onset, the genetic diagnostic testing revealed the presence of a mutation in the TGFB-I gene, typical of GCD2 in both cases, excluding GCD1. Patients who were clinically suspected of corneal dystrophy need a genetic confirmatory testing for certain diagnosis. Genetic test may help to find the specific mutation distinguishing between different phenotypic spectra with relative diagnostic and prognostic implications. The study demonstrates that the phenotypic spectrum of genetically confirmed granular corneal dystrophies in patients may change over time. Since the R124H mutation has also been described in clinically asymptomatic individuals prior to LASIK, who then develop dramatic deposition, suggesting that this particular mutation and phenotype may be sensitive to, precipitated, or modified by central cornea trauma, a careful familial anamnesis excluding cornel dystrophies and specific preoperative genetic test are recommended prior to LASIK.